2018
DOI: 10.3390/molecules23040795
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Use in Agriculture and Its Consequential Resistance in Environmental Sources: Potential Public Health Implications

Abstract: Due to the increased demand of animal protein in developing countries, intensive farming is instigated, which results in antibiotic residues in animal-derived products, and eventually, antibiotic resistance. Antibiotic resistance is of great public health concern because the antibiotic-resistant bacteria associated with the animals may be pathogenic to humans, easily transmitted to humans via food chains, and widely disseminated in the environment via animal wastes. These may cause complicated, untreatable, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
758
1
23

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,138 publications
(785 citation statements)
references
References 275 publications
(325 reference statements)
3
758
1
23
Order By: Relevance
“…It may takes a long while before implementation. The different approaches used in different countries leads to inconsistency results which are difficult to compare at national, regional and international perspectives [86]. The results reported do not conform to the international reporting systems since there is no appropriate system for data collection, identifications, coordination and reporting [90].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It may takes a long while before implementation. The different approaches used in different countries leads to inconsistency results which are difficult to compare at national, regional and international perspectives [86]. The results reported do not conform to the international reporting systems since there is no appropriate system for data collection, identifications, coordination and reporting [90].…”
Section: Discussionmentioning
confidence: 96%
“…This coupled with low awareness on AMU and AMR is likely to further exacerbate the burden of AMR in the region. This review has revealed high prevalence of AMR, including MDR bacteria in the environment, probably associated with anthropogenic activities, application of manure in farming activities and agricultural wastes from community [61,69,85,86]. There is potential spillage of resistant isolates from sewage, humans, companion and domestic animals and industries to the environment [69,87].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, bacterial resistance has been reported in all WHO regions and identified for every antimicrobial drug developed to date [1,2]. In particular, the recent increase in bacterial strains showing resistance to almost all classes of antibiotics commonly used in human medicine has become a serious threat to public health worldwide [3,4]. Therefore, there is an urgent need to develop alternatives to conventional antibiotics for use in the treatment of infectious diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the systematic intake of antibiotic-containing food can have various adverse effects, such as allergic reactions, metabolic disorders, dysbiosis, suppression of enzyme activity, change in microflora, etc. 5 Moreover, the problem of the emergence and spread of multi-resistant forms of microorganisms currently exists on a global scale. 6 In this regard, the problem of the safety of livestock products is becoming increasingly important.…”
Section: Introductionmentioning
confidence: 99%